2022
DOI: 10.55178/idm.v2i3.211
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi Sekolah, Kompetensi Guru Dan Motivasi Guru Terhadap Kinerja Guru Di Sma Negeri Kecamatan Samalanga Kabupaten Bireuen

Abstract: Tujuan penelitian ini adalah untuk mengetahui a) pengaruh budaya organisasi sekolah terhadap kinerja guru, b) pengaruh kompetensi guru terhadap kinerja guru, c) pengaruh motivasi guru terhadap kinerja guru, dan d) pengaruh faktor-faktor budaya organisasi, kompetensi guru, dan motivasi guru terhadap kinerja guru SMA Negeri se-Kecamatan Samalanga Kabupaten Bireuen.  Objek penelitian adalah 50 guru PNS (ASN) yang bekerja sebagai guru di SMA Negeri se-Kecamatan Samalanga Kabupaten Bireuen tahun 2020.  Dengan metod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…These results prove that the higher the organizational culture, the more it improves teacher performance in real terms It can be interpreted that there is a positive influence of organizational culture on improving teacher performance in MTs Negeri 8 Sragen. Furthermore, this is in line with previous research conducted by (Nurlaili, Apridar et al, 2019) explaining that organizational culture has a positive and significant effect on the work environment and teacher performance, in addition to the above opinions, this is also in line with the research conducted by (Muntasir & A.samad, 2021) explained: (1) The organizational culture that has been run in the Samalanga Kabupaen Bireuen District State High School school, according to the perception of teachers has been going well in supporting teacher performance. (2) Verifiative research results based on causality analysis between variables prove; a) there is a significant influence of organizational culture on teacher performance.…”
Section: B the Influence Of Organizational Culture On Teacher Perform...supporting
confidence: 89%
See 1 more Smart Citation
“…These results prove that the higher the organizational culture, the more it improves teacher performance in real terms It can be interpreted that there is a positive influence of organizational culture on improving teacher performance in MTs Negeri 8 Sragen. Furthermore, this is in line with previous research conducted by (Nurlaili, Apridar et al, 2019) explaining that organizational culture has a positive and significant effect on the work environment and teacher performance, in addition to the above opinions, this is also in line with the research conducted by (Muntasir & A.samad, 2021) explained: (1) The organizational culture that has been run in the Samalanga Kabupaen Bireuen District State High School school, according to the perception of teachers has been going well in supporting teacher performance. (2) Verifiative research results based on causality analysis between variables prove; a) there is a significant influence of organizational culture on teacher performance.…”
Section: B the Influence Of Organizational Culture On Teacher Perform...supporting
confidence: 89%
“…Another factor that affects teacher performance is organizational culture. According to (Nurlaili, Apridar et al, 2019) explain that organizational culture has a positive and significant influence on the work environment and teacher performance, in addition to the above opinions, this is in line with the research conducted by (Muntasir & A.samad, 2021) explaining the results of verifiative research based on causality analysis between proven variables; a) there is a significant influence of organizational culture on teacher performance, research conducted (Meri., 2020) explains There is a significant influence of organizational culture on teacher performance, other research (Fitria, 2018) explains that there is a direct influence of organizational culture on teacher performance. Based on several opinions concluded that organizational culture has a positive and significant effect on teacher performance, this shows that organizational culture is one factor that determines teacher performance.…”
Section: Introductionsupporting
confidence: 70%